Associations between Age, Years in Post, Years in the Profession and Personal Experience of Mental Health Problems in UK Mental Health Nurses. (3rd August 2017) - Oates, Jennifer; Drey, Nicholas; Jones, Julia
ABSTRACT: Nurses' mental health is of paramount importance, both in terms of patient safety and the sustainability of the workforce. Age, years in the profession, in post and personal experience or exposure to mental health problems are relevant to the mental health nursing workforce crisis in the United Kingdom. This study aimed to determine the relationship between age, years in the profession and post and self-reported experience of mental health problems using an online cross-sectional survey of 225 UK mental health nurses. Number of years in post was inversely correlated with overall experience of mental health problems, particularly living with someone else with mental health problems. Those with experience of living with someone with mental health problems had significantly fewer years of professional experience than those without. This article discusses possible explanations for this phenomenon and makes the case for future research on the topic.